Immediate and late inflammatory and bone healing response post implantation of self-tapping and self-drilling osteosynthesis screws - Regina Momesso, N.; Cristina Biguetti, C.; Estevão Costa, B.; Lucio Calazans Duarte, G.; Akemi Matsumoto, M. [UNESP]; Domingos Ribeiro Junior, P. (Elsevier, 2023)
The aim of this study was to comparatively analyse osseointegration after the implantation of self-tapping screws (STS) and self-drilling screws (SDS). Thus, 24 four-month-old male Wistar rats, received SDS and STS screws in their left and right tibias, respectively. Sample collection was performed immediately at 0 hours (0h), two, seven, and 21 days after implantation (2d, 7d, 21d). Samples from immediately and 21 days after were analysed by micro computed tomography (MicroCT). All time points were evaluated by histology (Haematoxylin and Eoisin and Goldner's Trichrome) and immunohistochemistry for tartrate-acid resistant phosphatase positive (TRAP+) osteoclasts. MicroCT images revealed an intimate contact between bone and each type of screw at 0h. However, SDS group presented decreased bone volume (BV, mm3) at 21 days in comparison with STS. Both SDS and STS post implantation presented areas of suitable new bone formation surrounding screw threads from seven days, and inflammation decreased from two to 21 days. Also, TRAP+ osteoclasts were mainly identified at seven days in both STS and SDS groups, particularly surrounding areas of pressure, with significant differences between groups. In conclusion, differences in shape and insertion technique for SDS and STS screws did not affect immediate and late inflammatory and bone healing response post implantation in this animal model. Both osteosynthesis screws allowed satisfactory post-surgical outcomes.
Keywords: Bone plates; Osteotomy; Trauma